2015
DOI: 10.1515/ijek-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Actual Problems Of Business Risk In SME Segment. Case Study From Slovakia

Abstract: The aim of this article was to define, quantify and compare the significant attributes of business risk for small and medium-sized enterprises (SMEs) in the selected regions of Slovakia. The data was collected through a questionnaire. The whole research was conducted in the Bratislava region on a sample of 102 SMEs, in the region of Trencin on a sample of 105 SMEs and in the Zilina region on a sample of 168 SMEs. Thus we compared important factors of business risk in the most economically developed region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Entrepreneurs in each region were threatened by the market risk, the most intense in Bratislava region; its average in Bratislava was 56, while 51.30 in Žilina and 53.27 in Trenčín region. Our research confirmed the results by Belás et al (2015c).…”
Section: Financial Risk Of Smes In Slovakiasupporting
confidence: 93%
See 1 more Smart Citation
“…Entrepreneurs in each region were threatened by the market risk, the most intense in Bratislava region; its average in Bratislava was 56, while 51.30 in Žilina and 53.27 in Trenčín region. Our research confirmed the results by Belás et al (2015c).…”
Section: Financial Risk Of Smes In Slovakiasupporting
confidence: 93%
“…On that topic many authors (e.g. , 2015c, Dong, 2014, Cheng & Tang, 2012 etcs declare that SMEs have problems with access to funding which leads to a real problem in to their growth worldwide. The lack of finance is categorized as one of the types of financial risks and this is the reason why we connect insufficient capital of SMEs with financial risks.…”
Section: Difficulties In Financing Of Smes -Literature Reviewmentioning
confidence: 99%
“…The results of our research are conformal with the results of Irwin and Scott (2010), Sobekova Majkova (2011), Belás et al (2015a), Cheng and Tang (2012), Shi (2012), Majkova (2008, Jinjarak and Wignaraja (2016), Rostamkalaei and Freel (2015), Oliveira and Fortunato (2006), Bottazzi, et. al.…”
Section: Figure 2 Number Of Answers On the Question Which Loan Critesupporting
confidence: 91%
“…It was found out that compared with pre-crisis period, the performance of SMEs in Slovakia have decreased by at least 15%. (Belás, Bilan, Ključnikov, Vincúrová and Macháček, 2015).…”
Section: Resultsmentioning
confidence: 99%